2019
DOI: 10.1101/661876
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Methylation at nucleotide C62 in spliceosomal RNA U6 alters mRNA splicing which is important for embryonic development

Abstract: DCB) 9 3 31under investigation. Alternative splicing of mRNA transcripts of genes is tissue and time specific 32 throughout life, although this process occurs everywhere in the body according to local tissue 33 needs and signals. The spliceosome, the large ribonucleoprotein complex that carries out splicing, 34 is biochemically modified by small noncoding RNAs, which is important for its structure and 35 function. Here we show that the amount of 2'-O-ribose methylation at nucleotide C 62 in 36 spliceosomal RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…These observations strongly suggest that snoRNAs and snRNAs are necessary for normal cardiac development. Furthermore, Ogren et al reported that methylation in the target region of SNORD94 on U6 is decreased in right ventricular myocardium tissue of infants with TOF compared with that of the control (Ogren et al, 2019). Additionally, cell culture experiments revealed that, by changing the levels of SNORD94, a corresponding change in methylation at C 62 within the snRNA U6 is produced.…”
Section: Role Of Snornas In Chdmentioning
confidence: 99%
“…These observations strongly suggest that snoRNAs and snRNAs are necessary for normal cardiac development. Furthermore, Ogren et al reported that methylation in the target region of SNORD94 on U6 is decreased in right ventricular myocardium tissue of infants with TOF compared with that of the control (Ogren et al, 2019). Additionally, cell culture experiments revealed that, by changing the levels of SNORD94, a corresponding change in methylation at C 62 within the snRNA U6 is produced.…”
Section: Role Of Snornas In Chdmentioning
confidence: 99%